Bioplastics for packaging in cosmetic sector towards a circular bioeconomy model - matarazzo, agata; Vizzini, Ludovica; arfo’, sergio; Pulvirenti, Edoardo (Archives of Business Research, 2020)
What do you want to do ? New mail Copy The Italian cosmetic industry is experiencing a period of constant growth. The materials used for industrial packaging are often produced in compliance with the hygiene standards imposed by the rules of the sector but without looking at the environmental aspect, how they are produced and how these packaging will be disposed of. In recent years, consumers’ environmental awareness has increased thanks to fast and accessible media, like the internet, and to a greater consciousness of the institutions. The average consumer is no longer satisfied with the generic product found at the point of sale, but he informs himself, evaluates, and relies on companies that embrace the culture of sustainability. The aim of this paper is the analysis of the technological and environmental advantages coming from the benefit of Bio-based polymers applied to the sector of cosmetic packaging, through a project of a new start up based on production of bioplastics for that sector.